A human factors contribution to countering insider threats: Practical prospects from a novel approach to warning and avoiding. Issue 1 (January 2017) - Hills, Mils; Anjali, Anjali
Abstract Any organisation is susceptible to a breach of security from outside: hacking, product contamination, theft of intellectual property and so on. Although all of these are risks to an organisation and can be highly deleterious to its financial health and reputation, the threat posed by a malevolent insider can be even more challenging. Although there has been a large quantity of academic articles and industry surveys produced on the theme of Insider Threats, the majority of this published work is descriptive or details the effects of insiders' actions. This article provides initial thoughts around some practical and pragmatic steps to beginto gain clarity on the challenge of insider threat and how organisations may draw on novel approaches to increasing early warning, response and mitigation against Insider Threats. The article also discusses the importance of security culture and risk communication.